Interleukin-23 and Th17 Cells in the Control of Gut Inflammation - Ivan Monteleone; Francesco Pallone; Giovanni Monteleone (Hindawi Limited, 2009)
Crohn's Disease and Ulcerative Colitis, the major forms of inflammatory bowel diseases (IBDs) in humans, have been traditionally associated with exaggerated and poorly controlled T helper (Th) type 1 or Th2 cell response, respectively. More recent studies have, however, shown that IBDs are also characterized by a sustained production of cytokines made by a distinct lineage of Th cells, termed Th17 cells. The demonstration that Th17-related cytokines cause pathology in many organs, including the gut, and that expansion and maintenance of Th17 cell responses require the activity of IL-23, a cytokine made in excess in the gut of IBD patients has contributed to elucidate new pathways of intestinal tissue damage as well as to design new therapeutic strategies. In this review, we discuss the available data supporting the role of the IL-23/Th17 axis in the modulation of intestinal tissue inflammation.